Stochastic Lyapunov Functions for a System of Nonlinear Difference Equations - Dzhalladova, I. A. (Ukrains’kyi Matematychnyi Zhurnal, 2002)
We study problems related to the stability of solutions of nonlinear difference equations with random perturbations of semi-Markov type. We construct Lyapunov functions for different classes of nonlinear difference equations with semi-Markov right-hand side and establish conditions for their existence.